Conducting business in China and India : a comparative and contextual analysis - Sardana, Deepak; Zhu, Ying (Palgrave Macmillan Asian business series., 2017)
This book takes a holistic approach to explore how business is being conducted in China and India, and to analyze the factors that influence business decisions in present times. In doing so the book seeks to develop a fuller understanding of the present 'context' within the two Asian nations, drawing upon a complete understanding of the culture, history and behaviour of the society and its institutions. The authors probe an area that has not been widely addressed before and seek to provide a finer analysis of the influences behind day-to-day business operations. This study has widespread appeal as it covers business processes at three different levels: macro-level, including government policies and institutions; meso-level, organisations and communities; and micro-level, individuals within business. Not only appealing to scholars, senior executives, business professionals and policy-makers, this book will also provide an interdisciplinary examination of how business is conducted in China and India, and will be valuable to anyone with a general interest in Asian business.- Resumé vydavatel